Planktonic foraminiferal biostratigraphy and correlation of the aquia formation in the type area, along the Potomac River, Virginia - Faris, Craig Duncan (Virginia Polytechnic Institute and State University, 1982)
Planktonic Foraminifera were examined from the Aquia Formation (Late Paleocene) from 2 localities in the Aquia type area along the Potomac River 7 miles southeast of Stafford, Virginia to: identify taxa present, and to effect biostratigraphic correlation with other Paleocene studies on the Virginia Coastal Plain. Two genera and twenty-two species were recovered, allowing recognition of the Globorotalia pseudomenardii and Globorotalia velascoensis zones, and correlation with The Oak Grove Core, 23 miles to the southeast (Gibson, et al. 1980), and a Pamunkey River locality 50 miles to the south (Seaton, 1982). This correlation shows equal thicknesses of the Aquia within zonal boundaries over the Potomac River - Oak Grove - Pamunkey River area, suggesting uniform rates of Aquia sedimentation in this portion of the Salisbury Embayment. Correlation of the Oak Grove Core, which was zoned via the Tertiary NP zonation indicates the presence of NP zones 5,6-?7,8,9 in the Aquia type area. Master of Science